Differential Role of Cathepsins S and B In Hepatic APC-Mediated NKT Cell Activation and Cytokine Secretion - de Mingo Pulido, Álvaro; de Gregorio, Estefanía; Chandra, Shilpi; Colell, Anna; Morales, Albert; Kronenberg, Mitchell; Marí, Montserrat (Frontiers in Immunology, 2018)
Natural killer (NKT) T cells exhibit a specific tissue distribution, displaying the liver the highest NKT/conventional T cell ratio. Upon antigen stimulation, NKT cells secrete Th1 cytokines, including interferon γ (IFNγ), and Th2 cytokines, including IL-4, that recruit and activate other innate immune cells to exacerbate inflammatory responses in the liver. Cysteine cathepsins control hepatic inflammation by regulating κB-dependent gene expression. However, the contribution of cysteine cathepsins other than Cathepsin S to NKT cell activation has remained largely unexplored. Here we report that cysteine cathepsins, cathepsin B (CTSB) and S (CTSS), regulate different aspects of NKT cell activation. Inhibition of CTSB or CTSS reduced hepatic NKT cell activation and expansion in a mouse model after LPS challenge. In contrast, only CTSS inhibition reduced IFNγ and IL-4 secretion after in vivo α-GalCer administration. Accordingly, in vitro studies reveal that only CTSS was able to control α-GalCer-dependent loading in antigen presenting cells (APCs), probably due to altered endolysosomal protein degradation. In summary, our study discloses the participation of cysteine cathepsins, CTSB and CTSS, in the activation of NKT cells in vivo and in vitro.